Rancang Bangun Aplikasi Helpdesk Dilingkungan Institusi Untuk Efisiensi Kinerja User - Rahayu, Sri; Supriyanti, Dedeh; Fauzi, Ahmad (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
The helpdesk section is an officer who fixes all kinds of problems that occur in the office infrastructure, such as damaged computer hardware components and applications that don't work properly. Currently, the process of submitting complaints regarding computer problems is still carried out by meeting directly with the helpdesk department or using an office VoIP telephone. Then the helpdesk will record it in the register of reported problems, then send a team of technicians to repair the computer. When the computer has been repaired, it will be reported back to the helpdesk so that the status of the problem submission data is changed to complete repair. However, the process of submitting complaints is still considered manual and inefficient, so it does not rule out the possibility of obstacles or errors such as duplication of complaint data which occurs due to the large number of reports coming in at once, the data search process is repetitive and takes quite a long time. So it is necessary to build an IT helpdesk system application that uses the PHP programming language which is integrated with the database. This research produces an IT helpdesk system application that functions to make it easier for officers as one of the users in the process of collecting submission data and managing helpdesk data more effectively.